Prophage map of converting corynebacteriophage beta. - Laird, W (1976)
A prophage map for corynebacteriophage beta consisting of seven markers has been constructed and compared with the vegetative map. The mapping system utilizes heteroimmune double lysogens and capitalizes on the fact that these double lysogens are very unstable and throw off monolysogenic segregants. The prophage map, produced by characterizing the recombinant phage in these monolysogenic segregants, appears to be a cyclic permutation of the vegetative map with the gene for toxin at one end of the prophage map and the gene for phage immunity at the other. This permutation is in accord with the Campbell model for insertion of lambda phage if a site between the toxin and immunity genes in the vegetative map is designated as the phage attachment site. The position of the gene for toxin in the prophage map suggests that converting phages may have originated as specialized transducing phages for this gene.